The shadow of the world: excess and imprisonment in Diomedes: a trilogia do acidente, by Lourenço Mutarelli - André Cabral de Almeida Cardoso (Estudos de Literatura Brasileira Contemporânea)
The aim of this paper is to examine the way the aesthetics of film noir is appropriated by Lourenço Mutarelli in his graphic novel Diomedes: a trilogia do acidente . Torn between an attempt to represent the real and a strong impulse towards stylization, this aesthetics acts as a structuring element of the narrative, creating a world characterized by excess and degradation, from which apparently there is no way out.